Covariant quantization of the superstring - Berkovits, N. (American Institute of Physics (AIP), 2002)
After reviewing the Green-Schwarz superstring using the approach of Siegel, the superstring is covariantly quantized by constructing a BRST operator from the fermionic constraints and a bosonic pure spinor ghost variable. Physical massless vertex operators are constructed and, for the first time, N-point tree amplitudes are computed in a manifestly ten-dimensional super-Poincare covariant manner. Quantization can be generalized to curved supergravity backgrounds and the vertex operator for fluctuations around AdS(5) x S-5 is explicitly constructed.